A quantificação dos danos materiais na infortunística do trabalho - Santos, Bruna (2018)
Quantification of material damage due to accident and emergency medicine in Brazil, on the way that it is structured, allows the judge to make a decision starting from inappropriate technical investigation, substantiated, most times, on SUSEP (Superintendência de Seguros Privados), a list with private purpose, which parameters are not based on specific and scientific data. Decisions built on inappropriate report can be highly disastrous to the reparative system and trigger other issues of extraordinary proportions to victims of work accidents. The present research shows that employer’s civil obligation over work accidents and occupational diseases, united on the duty to indemnify, can be an instrument of law, used to cover the big number of accidents in Brazil. Seen that Brazil, since 70’s decade, when received the title of “world champion of work accidents”, still remains as one of the countries with higher level of mishaps on the planet, it is necessary to develop, or, at least, improve, legal ways to prevent work accidents. The law should worry about finding solutions capable of encourage the culture of prevention on work environment and increase employees’ level of health and safety. Besides life, that is, undoubtedly, the most precious asset of a human being, we should think of an economical perspective, where work accidents’ cost represents an expense of R$20 billions every year, according to studies. It is spent by the State, companies and its own employees. The consequences of accident and emergency medicine in Brazil represent, therefore, an obstacle to the country’s economical development, demanding study and analysis of the regulation, especially about material damage repair.